Ferrite Nanoparticles-Based Reactive Oxygen Species-Mediated Cancer Therapy - Yu, Shancheng; Zhang, Huan; Zhang, Shiya; Zhong, Mingli; Fan, Haiming (Frontiers in Chemistry, 2021)
Ferrite nanoparticles have been widely used in the biomedical field (such as magnetic targeting, magnetic resonance imaging, magnetic hyperthermia, etc.) due to their appealing magnetic properties. In tumor acidic microenvironment, ferrite nanoparticles show intrinsic peroxidase-like activities, which can catalyze the Fenton reaction of hydrogen peroxide (H_2 O_2) to produce highly toxic hydroxyl free radicals (∙OH), causing the death of tumor cell. Recent progresses in this field have shown that the enzymatic activity of ferrite can be improved via converting external field energy such as alternating magnetic field and near-infrared laser into nanoscale heat to produce more ∙OH, enhancing the killing effect on tumor cells. On the other hand, combined with other nanomaterials or drugs for cascade reactions, the production of ROS can also be increased to obtain more efficient cancer therapy. In this review, we will discuss the current status and progress of the application of ferrite nanoparticles in ROS-mediated cancer therapy, and try to provide new ideas for this area.